2012
DOI: 10.4081/ejh.2012.e48
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective potential of histamine on rat small intestine and uterus

Abstract: The aim of this study was to improve knowledge about histamine radioprotective potential investigating its effect on reducing ionising radiation-induced injury and genotoxic damage on the rat small intestine and uterus. Forty 10-week-old male and 40 female Sprague-Dawley rats were divided into 4 groups. Histamine and histamine-5Gy groups received a daily subcutaneous histamine injection (0.1 mg/kg) starting 24 h before irradiation. Histamine-5Gy and untreated-5Gy groups were irradiated with a dose of whole-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
(39 reference statements)
3
21
0
Order By: Relevance
“…In this regard, it was previously reported that histamine significantly protects in mice and rats two of the most radiosensitive tissues, small intestine and bone marrow, from high doses of gamma radiation [57]. In agreement with these data, histamine prevents functional and histological alterations of salivary glands produced by ionizing radiation [3].…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…In this regard, it was previously reported that histamine significantly protects in mice and rats two of the most radiosensitive tissues, small intestine and bone marrow, from high doses of gamma radiation [57]. In agreement with these data, histamine prevents functional and histological alterations of salivary glands produced by ionizing radiation [3].…”
Section: Introductionsupporting
confidence: 65%
“…Rats were maintained in our animal health care facility at 22 to 24°C and 50% to 60% humidity on a 12 h light/dark cycle with food and water available ad libitum . To determine the potential radioprotective effect of JNJ7777120 (Table 1) on small intestine, SMG and bone marrow we used the same experimental procedures that were previously described in detail [3,57]. Briefly, JNJ7777120 and JNJ7777120-5Gy groups received a daily subcutaneous JNJ7777120 injection (10 mg/kg) starting 24 h before irradiation and which continued until 3 days post-irradiation while untreated groups received saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 In this regard, it was reported that histamine significantly protects small intestine and bone marrow, from high doses of ionizing radiation, in 2 models of rodents. [5][6][7] In addition, histamine has the ability to prevent ionizing radiation-induced functional and histological alterations of salivary glands. 8 These features make histamine a suitable candidate as a radioprotector for patients undergoing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%